Living well, spending less : 12 secrets of the good life - Soukup, Ruth, 1978- (Grand Rapids, Michigan : Zondervan, 2014)
Ruth Soukup is the founder and writer of the blog Living Well, Spending Less. In this, her first book, she shares some of her own journey to finding the Good Life and also provides her readers with the practical advice and real life help they need to give their family a truly abundant life on a realistic and healthy budget.
Includes bibliographical references (pages 235-237).
Keywords: Finance, Personal; Budgets, Personal; Saving and investment